2006
DOI: 10.1001/archinte.166.8.909
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Prolonged Ventricular Repolarization in Hypertension

Abstract: Background: QT interval prolongation on the surface electrocardiogram (ECG) predicts cardiovascular complications in high-risk subjects, but its prognostic role in uncomplicated hypertension has been understudied. Methods: For up to 13 years (average, 5.3 years), we followed up 2110 white patients with initially untreated essential hypertension (mean±SD age, 49±12 years; 55% men) without prevalent cardiovascular or renal disease who underwent 12-lead ECG before therapy. We excluded patients with ECG abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 34 publications
(22 reference statements)
4
38
2
Order By: Relevance
“…5,7 QT interval prolongation (QTc X470 ms) was associated with 2.2-fold higher incidence rates of stroke among 471 Brazilian subjects with type 2 diabetes, 5 whereas no clear associations between QT interval prolongation (QTc X440 ms for men and QTc X450 ms for women) and the development of stroke were found among 2110 Italian subjects with essential hypertension. 7 This study is the first to examine this issue in a general population and clearly shows that QT interval prolongation can predict the incidence of stroke among Japanese men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 QT interval prolongation (QTc X470 ms) was associated with 2.2-fold higher incidence rates of stroke among 471 Brazilian subjects with type 2 diabetes, 5 whereas no clear associations between QT interval prolongation (QTc X440 ms for men and QTc X450 ms for women) and the development of stroke were found among 2110 Italian subjects with essential hypertension. 7 This study is the first to examine this issue in a general population and clearly shows that QT interval prolongation can predict the incidence of stroke among Japanese men.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recently, several epidemiological studies have also shown that QTc prolongation predicts the likelihood of cardiovascular disease (CVD), suggesting a possible link between QTc prolongation and atherosclerosis. [3][4][5][6][7] However, other epidemiological studies found no clear associations between QTc prolongation and the risk of CVD, [7][8][9][10] and there is significant uncertainty surrounding the association between QTc prolongation and CVD. Furthermore, current knowledge of the effects of QTc prolongation on CVD was derived mainly from studies conducted in Western populations; it is unclear to what extent these findings apply to Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…In the PIUMA study, Schillaci et al 27 studied 2110 hypertensive patients over a mean duration of 5.3 years. This study found a significant but weak association between corrected QT interval (QTc) and the Cornell voltage (r ¼ 0.06, P ¼ 0.006).…”
Section: Prolonged Qtc and Qrs Duration Predicts Prognosismentioning
confidence: 99%
“…8 The assessment of ventricular repolarization in hypertensive patients is important in terms of prognosis. A prolonged QT interval is a risk factor for ischemic heart disease in hypertensive subjects, 6 and in EH with left ventricular hypertrophy QT interval duration is independently associated with an increased risk of cardiovascular and all-cause mortality, even after effective antihypertensive treatment. 4 Multiple linear regression analysis identified the use of Ca-channel blockers as an independent predictor of QTcH length.…”
Section: Discussionmentioning
confidence: 99%
“…3 An abnormal ventricular repolarization, namely a prolonged QT interval, has been described in hypertensive patients 4,5 and represents a negative prognostic factor in these patients. 6,7 Patients at high risk of cardiovascular events, such as those with primary aldosteronism (PA), have been shown to have a prolonged QTc interval compared with essential hypertension (EH). 8 Patients with renal-artery stenosis are at increased risk of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%